Flavone-rich maize: an opportunity to improve the nutritional value of an important commodity crop - Casas, María I.; Duarte, Silvia; Doseff, Andrea I.; Grotewold, Erich (Frontiers in Plant Science, 2014)
Agricultural outputs have resulted in food production continuously expanding. Satisfying the needs of a fast growing human population, higher yields, more efficient food processing, and food esthetic value, resulted in crop varieties with higher caloric intake but lacking many phytochemicals important for plant protection and adequate human nutrition. The increasing incidence of chronic diseases such as obesity, diabetes and cardiovascular diseases, combined with social disparity worldwide prompted the interest in developing enhanced crops that can simultaneously address the two sides of the current malnutrition sword, increasing yield while providing added nutritional value. Flavones, phytochemicals associated with the beneficial effects of the Mediterranean diet, have potent anti-inflammatory and anti-carcinogenic activities. However, many Mediterranean diet-associated vegetables are inaccessible, or lowly consumed, in many parts of the world. Maize is the most widely grown cereal crop, yet most lines used for hybrid maize production lack flavones. As a first step towards a sustainable strategy to increasing the nutritional value of maize-based diets, we investigated the accumulation and chemical properties of flavones in maize seeds of defined genotypes. We show that the pericarps of the P1-rr genotype accumulate flavones at levels comparable to those present in some flavone-rich vegetables, and are mostly present in their C- and O-glycosylated forms. Some of these glycosides can be readily converted into the corresponding more active health beneficial aglycones during food processing. Our results provide evidence that nutritionally beneficial flavones could be re-introduced into elite lines to increase the dietary benefits of maize.